Critiquing the critics. A brief response to critics of restorative justice - Morris, Allison (The British journal of criminology, 2002)
Restorative justice has been subject to a number of attacks, both empirically and philosophically. This paper attempts to address some of these criticisms and suggests that they stem in part from misunderstandings about what restorative justice seeks to achieve and in part from demanding too much from restorative justice at this stage in its development. Attempts to evaluate restorative justice are also relatively recent. Critics, however, tend to either ignore the available research findings or to present them negatively. Critics also fail to contrast what restorative justice has achieved and may still achieve with what conventional criminal justice systems have achieved. Drawing from research, particularly from New Zealand, which has put restorative justice principles into practice to a greater extent than other jurisdictions, this review suggests that there are reasons to be relatively positive about the re-emergence of restorative justice